Effect of different transportation period on body weight loss, hematological and biochemical stress responses of sheep - Lendrawati, L.; Priyanto, R.; Jayanegara, A.; Manalu, W.; Desrial, D. (Diponegoro University, 2020)
The study was conducted to evaluate the duration of road transportation during 4, 8 and 12 hours on body weight loss, hematological and biochemical responses of sheep. Twenty-four male Javanese thin tailed sheep were separated into transported group (T4, T8 and T12) and non-transported group (NT4, NT8 and NT12). Transportation (T) groups were transported for 4, 8 and 12 h in the same open pick up with 0.28 m2/head of loading density. Body weight, haematological and biochemical blood profiles were determined. The results showed that increasing of transportation duration significantly increased (P<0.05) body weight loss and decreased (P<0.05) hematocrit, cortisol and glucose values in the blood. However, these values were in the normal range of sheep well-being. In conclusion, transported healthy Javanese thin tailed sheep under good condition without feed and water access up to 12 h can tolerate to adverse effect of transportation without disturbing their welfare.